MINORITAS MUSLIM PANAMA: MENUJU HARMONI KEBERAGAMAN PASCA PROYEK KANAL PANAMA - Fikri Surya Pratama Pratama (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
Despite being a minority, Panamanian Muslims have the longest historical history of any Central American region. Based on this, this article aims to explain the process of the entry of Islam into Panama, and explain how the development of da'wah civilization and the Muslim community in Panama, especially after the construction of the Panama Canal mega project. This type of research is qualitative research using historical research methods, with the following steps: 1) Heuristics or source collection through library research; 2) Source Criticism, namely comparison activities and selecting the validity of sources; 3) This interpretation or analysis stage has occurred either at the beginning of the research or during the post-research analysis process; 4) historiography or the last stage of this research in the form of historical scientific writings. The results of the study show that Islam entered Panam through Mandika slaves brought during the Spanish colonization there, but the development of Islamic da'wah only began to be intense during and after the construction of the canal, this da'wah was intensively carried out by Arab and South Asian immigrants, and reached its peak in 1850-1860's. Panama's constitution provides for religious freedom. Catholicism, Islam, Judaism, and several traditional Panamanian religions coexist in harmony. So far, Panama has given a positive picture of the Central America region which is very conducive and open to religious differences, especially in Islam.